Eliminating adhesive layers in silver metallization: A comparative study of glass cleaning methods for enhanced hydroxylation and adhesion - Abu Bakar, Amnani; Hashim, N.H; Tajuddin, H.A; Sadun, A.S; Abidin, Z.H.Z (elsevier, 2025)
Achieving robust adhesion and cost-efficiency in silver (Ag) thin films is pivotal for advancing microelectronic applications, owing to Ag’s exceptional low resistivity and thermal stability. This study investigates an optimized approach to hydroxylate glass substrates, effectively eliminating the reliance on conventional adhesive layers. Among five chemical cleaning methods evaluated, immersion in concentrated H₂SO₄, followed by thorough rinsing with deionized water and ultrasonication in ethanol, emerged as the most effective. This method produced highly hydrophilic surfaces with a contact angle (CA) of 6.6◦. The resulting Ag films, deposited via physical vapor deposition, demonstrated excellent adhesion without peeling, while also exhibiting smooth and uniform surfaces ideal for subsequent functionalization. By streamlining substrate preparation, this methodology enhances the fabrication efficiency of high-performance microelectronic devices, offering a practical and scalable solution for industrial applications.